Mass Media Campaigns' Influence on Prehospital Behavior for Acute Coronary Syndromes: An Evaluation of the Australian Heart Foundation's Warning Signs Campaign. Issue 7 (July 2015) - Bray, Janet E.; Stub, Dion; Ngu, Philip; Cartledge, Susie; Straney, Lahn; Stewart, Michelle; Keech, Wendy; Patsamanis, Harry; Shaw, James; Finn, Judith
Abstract : Background: The aim of this study was to examine the awareness of a recent mass media campaign, and its influence on knowledge and prehospital times, in a cohort of acute coronary syndrome (ACS) patients admitted to an Australian hospital. Methods and Results: We conducted 199 semistructured interviews with consecutive ACS patients who were aged 35 to 75 years, competent to provide consent, and English speaking. Questions addressed the factors known to predict prehospital delay, awareness of the campaign, and whether it increased knowledge and influenced actions. Multivariable logistic regression was used to examine the association between campaign awareness and a 1‐hour delay in deciding to seek medical attention (patient delay) and a 2‐hour delay in presenting to hospital (prehospital delay). The median age was 62 years (IQR=53 to 68 years), and 68% (n=136) were male. Awareness of the campaign was reported by 127 (64%) patients, with most of these patients stating the campaign (1) increased their understanding of what is a heart attack (63%), (2) increased their awareness of the signs and symptoms of heart attack (68%), and (3) influenced their actions in response to symptoms (43%). After adjustment for other predictors, awareness of the campaign was significantly associated with patient delay time of ≤1 hour (adjusted odds ratio [AOR]=2.25, 95% CI: 1.03 to 4.91, P =0.04) and prehospital delay time ≤2 hours (AOR=3.11, 95% CI: 1.36 to 7.08, P =0.007). Conclusions: Our study showed reasonably high awareness of the warning signs campaign, which was significantly associated with shorter prehospital decision‐making and faster presentation to hospital.